STUDY DETERMINAN ANTENATAL CARE (ANC) PADA IBU HAMIL DI PUSKESMAS MEDAN JOHOR TAHUN 2019 - Tetty Junita Purba; Gf Gustina Siregar (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
The Infant Mortality Rate (IMR) andmaternal mortality rate in Indonesiais still quite high. Most mother shave unregular prenatal care according to the schedule prescribed whichbya health worker it couse no impairing during pregnancy, feeling healthyof theirpregnancy. The pregnant mother have no pragnancy visiting becouse the pregnant mother have no problem on their prenancy,delivery and post-partum, it coused that mother of antenatal care have unknow condition of pregnancy. This studyaims to determine the determinant factor checking the Antenatal Careof pregnant women in the health centerof Medan Johor in 2019.This research is a quantitative survey with cross sectionals tudy. The population of this study were all pregnant womenin Puskesmas Medan Johor, amounting to 2115 people and thea sample is 95 people. The method of data analysis uses univariate, bivariate analysis with chi square test. Results ofthe study showed higher statistically educationis 69 people (72,6%), knowledgeis 71 people (74,7%) and husband supportis 65 people (68,4%) associated with the examination ofthe Antenatal Carein pregnant women in health centers Medan Year 2019.